Impact of Elevated Donor Troponin I as Predictor of Adverse Outcome in Adult Heart Transplantation: A Single-center Experience - Freundt, Miriam; Philipp, Alois; Kolat, Philipp; Rupprecht, Leopold; Friedrich, Christine; Hirt, Stephan W.; Haneya, Assad (The Thoracic and Cardiovascular Surgeon, 2018)
Background Due to globally increasing donor organ shortage, investigation of previously described risk factors for utilizing marginal donor hearts is needed. The aim of this study was to determine the impact of elevated donor serum troponin I (TnI) levels on outcome after heart transplantation (HTx).Methods Between January 1996 and August 2013, 161 patients were reviewed for donor TnI serum levels (>0.3 ng/mL was considered elevated), postoperative outcome parameters, 30-day mortality, and 1-, 3-, and 5-year survival.Results TnI levels were elevated in 45 (28.0%) donors. Recipients of hearts with elevated TnI had higher incidence of postoperative systolic dysfunction, prolonged inotropic support, prolonged mechanical ventilation, and longer intensive care unit (ICU) stay (p < 0.001). This group had higher 30-day mortality (22.2% vs 8.6%, p = 0.03) and lower 1-, 3-, and 5-year survival (56%, 53%, and 50% versus 82%, 76%, and 69%, p = 0.032). Elevated TnI was the only independent risk factor for 30-day mortality (odds ratio [OR] 3.63, 95% confidence interval [CI] 1.28–10.27, p = 0.015).Conclusions Elevated donor TnI serum concentration seems to be a marker for adverse outcome and increased short- and long-term mortality after HTx. Nevertheless, many other perioperative variables and parameters can be associated with outcome.
Keywords: heart transplantation; organ donor selection; transplant outcome; troponin I